UTILIZATION OF POWTOON TO IMPROVE STUDENT LEARNING OUTCOMES AT CITIZENSHIP EDUCATION COURSE - Edwin Nurdiansyah; Emil El Faisal; Sulkipani Sulkipani (Sriwijaya University Learning and Education International Conference, 2018)
This literature review aims to show the subject of Citizenship Education is one of the compulsory subjects at university level, it shows if Citizenship Education has an important role in the effort to realize the goal of education in Indonesia. But in practice in the field, sometimes this subject is considered boring by the students so that the achievement of existing learning in Citizenship Education is not achieved optimally. What makes this subject boring is the use of lecture methods in lectures, civic education lecturers tend to often use lecture methods without accompanied by the use of other media. To overcome this, in lecturers lectures can use learning media that are able to attract interest and generate motivation from students. PowToon as a multimedia application can be used as a learning media, in addition to very easy to use this application also has a variety of interesting features in it. It is hoped that using PowToon as a learning medium can realize what is expected from civic education learning.